Parody and Ironic Juxtaposition in Toru Takemitsu’s Music for the Film, Rising Sun (1993) - Koozin, Timothy (Journal of Film Music, 2010)
Toru Takemitsu created music for more than a hundred films, but only one was for a major Hollywood studio, Rising Sun (1993) with Sean Connery and Wesley Snipes. In his music for Rising Sun, Toru Takemitsu contrasts and juxtaposes exotic, popular, and modernist musical elements to depict the cinematic drama in ways that are analogous to procedures that have been noted in dramatic music by Debussy, Stravinsky, and Messiaen, composers Takemitsu is known to have admired. At the same time, Takemitsu references traditional Japanese music, American jazz, and musical genres of the crime drama and film noir to construct a musical narrative of evocative color, irony, and dark humor. Rising Sun is based on a Michael Crichton novel that was criticized as a reactionary statement against Japanese economic aggression. This study shows how Takemitsu’s compelling music ironically projects the themes of economic warfare and cultural division in the film while also providing resistance through a subtle projection of his own humanistic worldview. The considerable changes that director and screen co-writer, Philip Kaufman made in adapting the novel dramatically alter the underlying social/political implications in the story. The analysis examines how this transformation from the original story is communicated through cultural codes embodied in preexisting music layered in the soundtrack along with Takemitsu’s originally composed textures, by artists including Cole Porter, Duke Ellington, Latino rappers Cypress Hill, and the seventies New Wave band, the B-52s.